Tutela coletiva e interesses metaindividuais - Telles, Douglas Silva (2009)
This study aims at the analysis and discussion about the collective authority in Brazilian law through the exposure of plural interest (diffuse, collective and individual homogeneous), with its existing forms, evolution and extension. How to guardianship collective, the exhibition begins by presenting the popular action provided for in Law no. 4.717/1965, followed by action civil service, provided by Law no. 7.347/1985, and finally through collective action, approved in Brazilian law by the Code of Consumer Protection, Law no. 8.078/1990. It used the Class Action North America as a reference to explain the origin and form of collective actions in Brazilian law. Finally, it proposes discussion as the existence of a single lawsuit nature of collective defense for the interests of all metaindividuais and extent of legitimacy, so that the Brazilian collective action can be judged by a single individual from the admissibility of such action, just as occurs in the Office of reference.